A utilização da estrutura de tamanho para avaliar o impacto do pastejo de gado e da monocultura de eucalipto sobre populações de espécies arbóreas - Souza, Iliane Freitas de (Universidade do Vale do Rio do Sinos, 2009)
This studied was carried in ten riparian forest fragments located southern Brazil. Of the ten riparian forests selected for study, five were embedded in pasturelands and five in eucalyptus plantations. We assessed the population sustentability of Campomanesia rhombea, Diospyros incontans, Myrciaria cuspidata and Sebastiania commersoniana through analyses of size structure, which were carried out at two scales. At a local scale, we consider populations in fragments surrounded by pastures or eucalyptus forest plantations, and at a regional scale we also consider larger forest tracts taken as reference areas (Rio Grande do Sul Forest Inventory databank). At local scale, the populations in fragments embedded by eucalyptus plantations prevailed small size classes individuals, and in areas exposed to cattle ranching, the same species seem to have a recurring failure of small individuals. Regional analyses included only established individuals with DBH > 1.6 cm. In this scale, populations in fragments surrounded by
Keywords: estrutura de tamanho; fragmentos de floresta ripária; monocultura de eucalipto; pastejo de gado; espécies arbóreas; eucalyptus plantations; riparian forest fragments; size structure; woody species; cattle ranching; Ciências Biológicas